Prognostic utility of self‐reported sarcopenia (SARC‐F) in the Multiethnic Cohort. Issue 2 (30th January 2022) - Wu, Anna H.; Setiawan, V. Wendy; Lim, Unhee; Tseng, Chiu‐Cheng; White, Kami K.; Shepherd, John; Lenz, Heinz Josef; Cheng, Iona; Stram, Daniel O.; Haiman, Christopher; Wilkens, Lynne R.; Le Marchand, Loïc
Abstract: Background: Age‐related loss in skeletal muscle mass, quality, and strength, known as sarcopenia, is a well‐known phenomenon of aging and is determined clinically using methods such as dual‐energy X‐ray absorptiometry (DXA). However, these clinical methods to measure sarcopenia are not practical for population‐based studies, and a five‐question screening tool known as SARC‐F has been validated to screen for sarcopenia. Methods: We investigated the relationship between appendicular skeletal lean mass/height 2 (ALM/HT 2 ) (kg/m 2 ) assessed by DXA and SARC‐F in a subset of 1538 (778 men and 760 women) participants in the Multiethnic Cohort (MEC) Study after adjustment for race/ethnicity, age, and body mass index (BMI) at the time of DXA measurement. We then investigated the association between SARC‐F and mortality among 71 283 (41 757 women and 29 526 men) participants in the MEC, who responded to the five SARC‐F questions on a mailed questionnaire as part of the MEC follow‐up in 2012–2016. Results: In women, SARC‐F score was significantly inversely associated with ALM/HT 2 after adjusting for race/ethnicity, and age and BMI at DXA ( r = −0.167, P < 0.001); the result was similar in men although it did not reach statistical significance ( r = −0.056, P = 0.12). Among the 71 000+ MEC participants, SARC‐F score ≥ 4, as an indicator of sarcopenia, was higher in women (20.9%) than in men (11.2%) ( P < 0.0001) and increased steadily with increasing age (6.3% in <70 vs. 41.3% in 90+ years old) ( P < 0.0001). SARC‐F score ≥ 4 was highest among Latinos (30.8% in women and 16.1% in men) and lowest in Native Hawaiian women (15.6%) and Japanese American men (8.9%). During an average of 6.8 years of follow‐up, compared with men with SARC‐F score of 0–1 (indicator of no sarcopenia), men with SARC‐F 2–3 (indicator of pre‐sarcopenia) and SARC‐F ≥ 4 had significantly increased risk of all‐cause mortality [hazard ratio (HR) = 1.00, 1.77, 3.73, P < 0.001], cardiovascular disease (CVD) mortality (HR = 1.00, 1.85, 3.98, P < 0.001), and cancer mortality (HR = 1.00, 1.46, 1.96, P < 0.001) after covariate adjustment. Comparable risk association patterns with SARC‐F scores were observed in women (all‐cause mortality: HR = 1.00, 1.47, 3.10, P < 0.001; CVD mortality: HR = 1.00, 1.59, 3.54, P < 0.001; cancer mortality: HR = 1.00, 1.30, 1.77, P < 0.001). These significant risk patterns between SARC‐F and all‐cause mortality were found across all sex–race/ethnic groups considered (12 in total). Conclusions: An indicator of sarcopenia, determined using SARC‐F, showed internal validity against DXA and displayed racial/ethnic and sex differences in distribution. SARC‐F was associated with all‐cause mortality as well as cause‐specific mortality.